The challenge of communicating reciprocal value promises: buyer-seller value proposition disparity in professional services - Baumann, Jasmin; Le Meunier-FitzHugh, Kenneth; Wilson, Hugh N. (Elsevier, 2017)
This study explores the communication of reciprocal value propositions in buyer-seller interaction and examines whether each party's value proposition is congruent with the value sought by their respective counterpart. Through 31 in-depth interviews with customers and salespeople from six professional service organizations, it was found that while both parties deliberately articulate value propositions, thereby initiating the co-creation process, there are some surprising disparities in the value dimensions offered by the salesperson. Although the customer's value proposition is largely consistent with the value sought by the seller, a marked discrepancy was encountered in the reverse case (i.e. between the seller's value proposition and the buyer's desired value). These findings indicate a significant misalignment between the seller's value proposition and actual co-creative behavior that can impede the subsequent collaboration and resource integration between the two parties, which could lead to customer dissatisfaction and potentially even service failure.